Effect of Rendering Virtual Vibrotactile Motion on the Perceived Lateral Force - Changhyeon Park; Seokmin Hong; Jaeyoung Park (IEEE Access)
In the present study, we investigate the effect of rendering virtual vibrotactile motion to the perception of lateral force during planar sweeping motion. The virtual vibrotactile motion was rendered by an algorithm to create the sensation of resistive lateral force utilizing illusory haptic effects. The direction of the virtual vibrotactile motion was the opposite of the hand-sweeping motion to create the sensation of resistive force. We conducted two experiments that mapped the lateral resistive haptic feedback rendered by the virtual vibrotactile motion and force feedback to the perceived force magnitude. In Experiment 1, the test was conducted for three reference stimulus force and two maximum signal intensities. The results indicate significant effect of the two experimental parameters. The perceived lateral force was significantly larger with the virtual vibrotactile motion than the force feedback only. Also, the increase in the maximum signal intensity led to a larger perceived lateral force. Experiment 2 tested the effect of vibrotactile signal envelope function on the perceived lateral force by conducting a comparative experiment for linear and logarithmic envelope functions. The experimental results indicate a significantly larger perceived lateral force for the logarithmic signal envelope function than the linear signal envelope function. Overall, this study suggests that rendering virtual vibrotactile motion at the fingertip during swiping motion can create the sensation of additive lateral force and that the perceived intensity can be controlled by modulating the vibrotactile signal intensity and the signal envelope functions.